Les Irlandais et les Chevaliers du travail à Montréal (1882-1890) - Bischoff, Peter (Le Québec et l'Irlande. Culture, histoire, identité, 2014)
Keywords: Chevaliers du Travail; Irlandais; Syndicats internationaux; Travail

Le Québec, les Irlandais et la politique au début du XXe siècle - Jolivet, Simon (Cap-aux-Diamants, 2007)
issued: 2007-24-00
Keywords: Irlandais

Analyse démogénétique de la contribution des fondateurs irlandais au peuplement du Québec et de ses régions - Letendre, Maude (Université Laval et Université du Québec à Chicoutimi, 2007)
Keywords: Irlandais

Entre nationalismes irlandais et canadien-français : Les intrigues québécoises de la Self Determination for Ireland League of Canada and Newfoundland - Jolivet, Simon (Canadian Historical Review, 2011)
Number: 1
Keywords: Irlandais; Nationalisme

Les Irlandais à Montréal. Une présence marquante dès le XIXe siècle - Jolivet, Simon (Montréal en tête, 2013)
issued: 2013-23-00
Keywords: Irlandais; Saint-Patrick (paroisse)

Saint-Patrick et les paroissiens irlandais - Olson, Sherry (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Irlandais; Saint-Patrick (église); Sulpiciens; Églises

La représentation des troubles en Irlande du Nord dans les journaux québécois, 1969-1998 - Dufresne, Benjamin (Université du Québec à Trois-Rivières, 2024)
Keywords: Anglophones; Devoir (Le); Francophones; Montreal Gazette; Nationalisme; Presse (La)

Victor-Levy Beaulieu et la question nationale irlandaise - Poulin, André (Bulletin d'histoire politique, 2010)
issued: 2010-21-00
Keywords: Irlandais

Les deux questions irlandaises du Québec, 1898-1921: des considérations canadiennes-françaises et irlando-catholiques - Jolivet, Simon (Université Concordia, 2008)
Keywords: Irlandais

Orange, vert et bleu: les orangistes au Québec depuis 1849 - Jolivet, Simon (Bulletin d'histoire politique, 2010)
issued: 2010-21-00
Keywords: Irlandais

Irish-Catholic Leadership in Nineteenth Century Montreal - Leitch, Gillian (Cahiers d'histoire, 2003)
issued: 2003-23-00
Keywords: Irlandais

Port Cities in Crisis: Considering Urban Governance, Modernity and Migration in Mid-Nineteenth-Century Montreal and Liverpool in a Transnational Context - Horner, Dan (Cities Beyond Borders: Comparative and Transnational Approaches to Urban History, 2015)
Keywords: Irlandais

The harp and the shamrock: the two faces of Montreal's Irish community - Bâby, Françoise (The Westmount Historian, 2023)
Keywords: Griffintown; Irlandais

One long line of marvel: 200 years of Montreal's St. Patrick's parade - Hustak, Alan (Véhicule press, 2024)
Keywords: Irlandais; Processions

Survol d'une historiographie irlando-québécoise en développement - Jolivet, Simon (Mens, 2008)
issued: 2008-23-00
Keywords: Histoire; Irlandais

Irish Politics on Parade: The Clergy, National Societies, and St. Patrick's Day Processions in Nineteenth-century Montreal and Toronto - Trigger, Rosalyn (Histoire sociale / Social History, 2004)
Number: 74
Keywords: Irlandais; Processions

La mafia irlandaise de Montréal. L'histoire de la tristement célèbre gang de l'Ouest - O'Connor, D'Arcy; O'Connor, Miranda (Éditions La Presse, 2011)
Translators: _:n44987
Keywords: Criminalité; Irlandais

Montreal's Irish Mafia: the true story of the infamous West End Gang - O'Connor, D'Arcy; O'Connor, Miranda (Wiley, 2011)
Keywords: Criminalité; Irlandais

Griffintown: Identity and Memory in an Irish Diaspora Neighbourhood - Barlow, Matthew (UBC Press, 2017)
Keywords: Griffintown; Irlandais

Le vert et le bleu: identité québécoise et identité irlandaise au tournant du XXe siècle - Jolivet, Simon (Presses de l'Université de Montréal, 2011)
Keywords: Irlandais; Nationalisme

Une ville - plusieurs reels: Montreal’s Multicultural Irish Soundscape - Tétrault-Farber, Jérémy (Université Concordia, 2019)
Keywords: Irlandais; Musique

"The House of the Irish": Irishness, History, and Memory in Griffintown, Montréal, 1868-2009 - Barlow, John Matthew (Université Concordia, 2009)
Keywords: Griffintown; Irlandais; Quartiers

An Irish heart: how a small immigrant community shaped Canada - Doyle Driedger, Sharon (HarperCollins Publishers, 2011)
Keywords: Griffintown; Irlandais; Quartiers

Feeling Comfortable? Les Anglo-Montréalais et leur ville - Radice, Martha (Presses de l'Université Laval, 2000)
Keywords: Anglophones; Britanniques; Irlandais; Écossais

Feeling Comfortable? The Urban Experience of Anglo-Montrealers - Radice, Martha (Presses de l'Université Laval, 2000)
Keywords: Anglophones; Britanniques; Irlandais; Écossais

Marrying ''the Other'': Trends and Determinants of Culturally Mixed Marriages in Québec, 1880-1940 - Gauvreau, Danielle; Thornton, Patricia (Études ethniques canadiennes / Canadian Ethnic Studies, 2015)
Number: 3
Keywords: Britanniques; Irlandais; Juifs; Mariage

Was Patrick James Whelan a Fenian and Did He Assassinate Thomas D'Arcy McGee? - Wilson, David A. (Irish Nationalism in Canada, 2009)
Keywords: Irlandais; McGee; Thomas d'Arcy; Nationalisme; Whelan; James

St. Patrick's and the Irish Catholics - Olson, Sherry (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Translators: _:n46469
Keywords: Communautés religieuses; Irlandais; Saint-Patrick (église); Sulpiciens; Églises

Population, identités sociales et vie quotidienne - Gauvreau, Danielle (Histoire de Montréal et de sa région, 2012)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Population, Social Identities, and Daily Life - Gauvreau, Danielle (Montreal: The History of A North American City, 2018)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Témoins discrets - Leclerc, Jean-François (Continuité, 2019)
issued: 2019-24-00
Keywords: Chinois; Grecs; Irlandais; Italiens; Juifs; Noirs; Patrimoine; Syriens

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (McGill-Queen's University Press, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."–
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Dynamiques démographiques à Montréal, 1880-1900 - Gauvreau, Danielle; Olson, Sherry; Thornton, Patricia (Le fait urbain, 2020)
Keywords: Britanniques; Femmes; Francophones; Fécondité; Irlandais; Mariage; Mortalité; Protestants; Travail; État civil

Les communautés culturelles du Plateau (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2018)
issued: 2018-22-00
Keywords: Allemands; Députés; Godin; Gérald; Grecs; Irlandais; Itinérance; Johns; Emmett (Père Pops); Juifs; Plateau Mont-Royal; Portugais; Poésie; Quartiers; Roumains